ANALISIS STRATEGI GURU DALAM MENERAPKAN METODE PENGULANGAN MELALUI AUDIO UNTUK MEMPERKUAT RETENSI MEMORI PADA SISWA DALAM PEMBELAJARAN BAHASA ARAB DI MADRASAH IBTIDAIYAH NURUL YAQIN - Alfath, Syahrul; Muspawi, Mohamad; Soleh, Warissuddin; Iryani, Eva; Hasani, Salman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze teacher's strategies in implementing the audio repetition method and identify supporting and inhibiting factors in strengthening students' memory retention in Arabic language learning. The research employed a descriptive qualitative approach with subjects including an Arabic teacher and eight 6th-grade students of MIS Nurul Yaqin selected through purposive sampling. Data collection techniques included participatory observation, in-depth interviews, and documentation studies. Data validity was ensured through source triangulation and member checks, while data analysis followed the interactive model of Miles, Huberman, and Saldana. The findings revealed that the teacher's strategy encompasses three stages: planning (material analysis and lesson plan adaptation), implementation (listening, imitating, repetition, and ice breaking), and evaluation (oral retention tests). Among the six ideal strategic steps, only one step was fully achieved (structured repetition scheme design), two steps were partially achieved (audio material planning and continuous evaluation), and three steps were not achieved (multimodal implementation, monitoring and differentiation, as well as cultural and religious integration). The primary supporting factor was student enthusiasm and lesson plan adaptability, while the dominant inhibiting factor was limited technical facilities (speaker quality). This study concludes that the audio repetition method effectively strengthens memory retention; however, its success depends on the availability of adequate infrastructure.